Longitudinal analysis of humoral and cellular immunity in SARS-CoV-2 exposed families - Dulovic, Alex; Rabsteyn, Armin; Remppis, Jonathan; Gentzcke, Irene K. E.; Mueller, Julia; Tuecks, Nadja; Becker, Matthias; Junker, Daniel; Kaiser, Philipp D.; Traenkle, Bjoern; Rothbauer, Ulrich; Walz, Juliane S.; et al. (Scientific reports, 2025)
Identification of previous SARS-CoV-2 infection typically relies on serology, yet T-cells play a key role in the adaptive immune response against SARS-CoV-2. Here, we investigated in parallel the SARS-CoV-2-specific as well as endemic human coronavirus-specific humoral and cross-reactive cellular responses in children and adults. We analyzed clinical data and blood samples from a family cohort of 96 children and 144 adults at 3-4 and 11-12 months after their first contact with SARS-CoV-2. Humoral response was assessed by a multiplex immunoassay with high sensitivity and specificity (MULTICOV-AB). Cellular responses were analyzed by IFN-γ ELISPOT using four different established epitope compositions (ECs) to discriminate between SARS-CoV-2 specific and HCoV cross-reactive T-cell responses. While the majority of adults had a combined serological and T-cell response, relatively more children had a T-cell response alone rather than a combined response. The magnitude of the T-cell response correlated with symptoms and the humoral response. In addition, SARS-CoV-2 infection significantly boosted the endemic coronavirus-specific cellular response. Overall, our data suggest discordant humoral and cellular responses, reflecting either abortive infection, cellular sensitization with rapid viral clearance or rapid antibody waning or a combination of these phenomena. Restricting epidemiologic analysis to SARS-CoV-2 serological data may underestimate rates of infection with or at least exposure to SARS-CoV-2 in children.
Veröffentlicht: 18. Juli 2025
Gesehen am 26.11.2025